2014
DOI: 10.1111/joa.12266
|View full text |Cite
|
Sign up to set email alerts
|

Development of the human infrahepatic inferior caval and azygos venous systems

Abstract: Differences in opinion regarding the development of the infrahepatic inferior caval and azygos venous systems in mammals centre on the contributions of 'caudal cardinal', 'subcardinal', 'supracardinal', 'medial and lateral sympathetic line' and 'sacrocardinal' veins. The disagreements appear to arise from the use of topographical position rather than developmental origin as criterion to define separate venous systems. We reinvestigated the issue in a closely spaced series of human embryos between 4 and 10 week… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
38
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(43 citation statements)
references
References 29 publications
2
38
0
Order By: Relevance
“…The black line shows the position of the aortic bifurcation (b; Hikspoors et al. ) or the temporal changes in greatest length of the embryo (divided by 10; C–F; O'Rahilly & Müller, ). Panel (B) shows that the entrance of the Wolffian duct into the cloaca/urogenital sinus (dotted red line; R 2 : 0.31) remained associated with segment 31–32 (S3–S4), whereas the tip of the urorectal septum (drawn red line; R 2 : 0.87) moved caudally to the level of the last coccygeal vertebra.…”
Section: Resultsmentioning
confidence: 99%
“…The black line shows the position of the aortic bifurcation (b; Hikspoors et al. ) or the temporal changes in greatest length of the embryo (divided by 10; C–F; O'Rahilly & Müller, ). Panel (B) shows that the entrance of the Wolffian duct into the cloaca/urogenital sinus (dotted red line; R 2 : 0.31) remained associated with segment 31–32 (S3–S4), whereas the tip of the urorectal septum (drawn red line; R 2 : 0.87) moved caudally to the level of the last coccygeal vertebra.…”
Section: Resultsmentioning
confidence: 99%
“…This model, which is applied in both human and veterinary embryology, states that the right-sided counterparts of three pairs of embryonic veins (i.e. the supracardinal, subcardinal and caudal cardinal veins) form the abdominal part of the caudal vena cava by means of fusion, anastomosis and asymmetric vascular degeneration during prenatal life (Huntington and McClure, 1920;Butler, 1927;Cornillie and Simoens, 2005;Cornillie et al, 2006;Hyttel, 2010;Sadler, 2012).However, a recent study revisiting the development of the inferior vena cava and vena azygos by means of three-dimensional reconstructions of human embryos (Hikspoors et al, 2015) has revealed various inaccuracies in the supracardinal system of Huntington and McClure (1920). All dorsal veins, formerly indicated as the supracardinal veins, must be considered as actual segments of the caudal cardinal system, which gradually adopts a different topography due to allometric growth of surrounding organs and tissues.…”
mentioning
confidence: 92%
“…However, a recent study revisiting the development of the inferior vena cava and vena azygos by means of three-dimensional reconstructions of human embryos (Hikspoors et al, 2015) has revealed various inaccuracies in the supracardinal system of Huntington and McClure (1920). All dorsal veins, formerly indicated as the supracardinal veins, must be considered as actual segments of the caudal cardinal system, which gradually adopts a different topography due to allometric growth of surrounding organs and tissues.…”
mentioning
confidence: 98%
See 2 more Smart Citations